Batter off dead - Day, Maddie (Day, Maddie. Country store mystery., 2022)
"Robbie and her new husband Abe O'Neill are enjoying a summer evening in the park with fellow townsfolk excited for some Friday night fireworks. In attendance are senior residents from Jupiter Springs Assisted Living including Roy Bird ... Roy is a member of his group home's knitting circle ... But when the lightshow ends, one of the knitters who sat with Roy is found dead, a puncture wound in her neck ... To help find the killer, Robbie's going to have to untangle the knotty relationships deep in the victim's past"--